2018
DOI: 10.1016/j.joca.2018.08.019
|View full text |Cite
|
Sign up to set email alerts
|

CGRP blockade by galcanezumab was not associated with reductions in signs and symptoms of knee osteoarthritis in a randomized clinical trial

Abstract: NCT02192190.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 26 publications
0
23
0
1
Order By: Relevance
“…In animal models, CGRP increases acute neurogenic inflammation and joint pain [107, 108]; whereas CGRP antagonists reduces osteoarthritis pain [61, 107, 109]. However, an anti-CGRP antibody (i.e., galcanezumab) failed to reduce osteoarthritis pain in patients [59, 60]. The lack of efficacy could be due to the inability of antibodies to reduce CGRP in the synovial joint to a therapeutic level.…”
Section: Discussionmentioning
confidence: 99%
“…In animal models, CGRP increases acute neurogenic inflammation and joint pain [107, 108]; whereas CGRP antagonists reduces osteoarthritis pain [61, 107, 109]. However, an anti-CGRP antibody (i.e., galcanezumab) failed to reduce osteoarthritis pain in patients [59, 60]. The lack of efficacy could be due to the inability of antibodies to reduce CGRP in the synovial joint to a therapeutic level.…”
Section: Discussionmentioning
confidence: 99%
“…Galcanezumab, a humanized monoclonal antibody, blocks calcitonin gene-related peptide (CGRP), that plays a role in pain in OA, and has been shown to be efficacious in migraine. In a doubleblind, placebo-and celecoxib-controlled randomized trial galcanezumab (doses 5 up to 300 mg subcutaneously every 4 weeks, twice), was investigated in 266 patients with painful knee OA 29 . Primary outcome was change in WOMAC pain after 8 weeks.…”
Section: Novel Treatmentsmentioning
confidence: 99%
“…Although repurposed Osteoporosis drugs show compelling results in pre-clinical testing in OA, clinical trials in late-stage OA, such as multiple phase III trials investigating calcitonin, have not yet demonstrated obvious benefits [ 45 ]. Galcanezumab, a monoclonal antibody targeting calcitonin gene-related peptide, was also unsuccessful in a phase II trial as it did not reduce signs or symptoms of knee OA [ 46 ].…”
Section: Current and Recent Targets In Chondroprotectionmentioning
confidence: 99%
“…Phase II trial is currently looking at denosumab in hand OA (NCT02771860).Calcium-reducing hormoneCalcitonin (osteoporosis drug)Two phase III trials did not show any clinical benefits to patients with symptomatic knee OA [45]. Anti-calcitonin gene-related peptide (migraine drug)Phase II study was terminated as interim assessment showed lack of efficacy [46]. BMPsBMP-7Phase I trial showed a symptom response and no dose limiting toxicity [47].…”
Section: Current and Recent Targets In Chondroprotectionmentioning
confidence: 99%